Evaluation of the ethnobotanical importance of Chromolana odorata (L.) R.M.King & H.Rob. and Mesosphaerum suaveolens (L.) Kuntze, two invasive alien plant species in southern and central Benin - Aikpon, Gorgias; Koura, Kourouma; Affokpon, Antoine; Ahanchede, Adam; Ganglo, Jean Cossi (Ethnobotany Research and Applications, 2026)
Background: Traditional medicinal knowledge remains a major source of healthcare for rural communities in developing countries. Chromolaena odorata and Mesosphaerum suaveolens, native to tropical America and invasive in Africa and Asia, are widely used in traditional medicine despite their ecological impacts. This study documents and compares the ethnobotanical uses, preparation methods, and cultural importance of these two invasive species. Methods: An ethnobotanical survey was conducted among 196 respondents selected using purposive sampling in rural communities of central and southern Benin. Data were collected from May to July 2025 using structured questionnaires to document uses, use categories, local names, plant parts, and preparation methods of both species. Relative Frequency of Citation (RFC) and Use Value (UV) indices were calculated to assess species importance. Associations between sociocultural groups and use categories were analysed using chi-square and Fisher’s exact tests, and Correspondence Analysis. Results: Twelve distinct vernacular names were identified for both species combined, five for C. odorata and seven for M. suaveolens, reflecting sociocultural variability in their designation. Three main categories of use were identified: medicinal, veterinary, and repellent. Among the different use categories, medicinal use was the most frequently cited for C. odorata (RFC = 55.6%) and M. suaveolens (RFC = 57.6%). Repellent use was markedly higher for M. suaveolens (RFC = 49.4%) than for C. odorata (RFC = 12.2%), while veterinary use remained limited for both species (RFC ≈ 11%). Leaves were the most used plant part, and preparation methods mainly included decoction, infusion, trituration, and inhalation. Statistical analyses revealed significant associations between sociocultural groups and use categories (p < 0.001). Conclusions: These findings highlight the widespread use of both species in traditional healthcare practices despite their invasive status. The reported uses of C. odorata and M. suaveolens highlight their potential relevance for the development of plant-based pest management strategies and emphasize the importance of documenting local ethnobotanical knowledge. Keywords: Ethnobotany, Chromolaena odorata, Mesosphaerum suaveolens, traditional medicine, medicinal plants, indigenous knowledge.